Worry angels - Brahmachari, Sita (Edinburgh: Barrington Stoke, 2017)
Everyone says I have ''anxiety''. Too much anxiety for the big school in this new city. So I'm at Grace's art school instead, where we craft and draw, grow and cook. Today I baked a cake and planted seeds. Grace is making worry angels for us all. I think she paints her kindness into them. A girl from Syria starts tomorrow. I learned to say ''ahlan wa sahlan'' to welcome her in Arabic. -- Cover
Keywords: Children's stories